Studying the relationship between employee empowerment strategy and the quality of services provided in private Syrian companies (A case study of Al-Fadel Exchange Company) - كعده, عباس; كندة علي ديب; ديمة ماخوس (Latakia University Journal - Economic and Legal Sciences Series, 2023)
This study aimed to reveal the impact of the strategy of empowering employees on the quality of services provided in the branches of Al-Fadil Exchange Company, a private joint stock company. Mrs. Zainab / - Aleppo - Lattakia - Hama - Daraa), where a simple random sample was drawn from the company's branches with a size of (79 individuals) out of the total study population of (135 employees), and the practical study was conducted using appropriate statistical methods, and the study concluded By testing hypotheses and analyzing them to a set of results; The most prominent of which was the company’s clear interest in the strategy of empowering employees and the quality of the services it provides. The results of the study also showed that the strategy of empowering employees applied in the company’s branches clearly contributes to improving the quality of the services provided. After analyzing the results, the study recommended a set of recommendations to enhance the strategy of empowering employees. In order to ensure the improvement of their performance and the quality of services provided by the company.